Anti-NT5c1A Autoantibodies as Biomarkers in Inclusion Body Myositis - Amlani, Adam; Choi, May Y.; Tarnopolsky, Mark; Brady, Lauren; Clarke, Ann E.; Garcia-De La Torre, Ignacio; Mahler, Michael; Schmeling, Heinrike; Barber, Claire E.; Jung, Michelle; Fritzler, Marvin J. (Frontiers in Immunology, 2019)
OBJECTIVE: Sporadic Inclusion Body Myositis (sIBM) is an inflammatory myopathy (IIM) without a specific diagnostic biomarker until autoantibodies to cytosolic 5’-nucleotidase 1A (NT5c1A/Mup44) were reported. The objectives of our study were to determine the sensitivity and specificity of anti-NT5c1A for sIBM, demonstrate demographic, clinical and serological predictors for anti-NT5c1A positivity and determine if anti-nuclear antibody (ANA) indirect immunofluorescence (IIF) staining on HEp-2 cells is a reliable screening method for anti-NT5c1A. METHODS: Sera from sIBM patients and controls were stored at -80C until required for analysis. IgG antibodies to NT5c1A were detected by an addressable laser bead immunoassay (ALBIA) using a full-length human recombinant protein. Autoantibodies to other autoimmune myopathy antigens (Jo-1, OJ, TIF1y, PL-12, SAE, EJ, MDA5, PL7, SRP, NXP2, MI-2) were detected by line immunoassay (LIA), chemiluminescence immunoassay (CIA) or enzyme linked immunoassay (ELISA) and ANA detected by IIF on HEp-2 substrate. Demographic, clinical and serological data were obtained by chart review. RESULTS: 43 patients with sIBM, 537 disease control patients with other autoimmune, degenerative and neuromuscular diseases, and 78 healthy controls were included. 48.8% (21/43) of sIBM patients were positive for anti-NT5c1A. The overall sensitivity, specificity, positive predictive value, and negative predictive value of anti-NT5c1A for sIBM was 0.49, 0.92, 0.29, and 0.96, respectively. Compared to sIBM, the frequency of anti-NT5c1A was lower in both the disease control group (8.8%, OR 0.10 [95%CI: 0.05-0.20], p<0.0001) and in the apparently healthy control group (5.1%, OR 0.06 [95%CI: 0.02-0.18], p<0.0001). In the univariable analysis, sIBM patients with more severe muscle weakness were more likely to be anti-NT5c1A positive (OR 4.10 [95% CI: 1.17, 14.33]), although this was not statistically significant (adjusted OR 4.30 [95% CI: 0.89, 20.76], p=0.069) in the multivariable analysis. The ANA of sIBM sera did not demonstrated a consistent IIF pattern associated with anti-NT5c1A. CONCLUSIONS: Anti-NT5c1A has moderate sensitivity and high specificity for sIBM using ALBIA. The presence of anti-NT5c1A antibodies may be associated with muscle weakness. Anti-NT5c1A antibodies were not associated with a specific IIF staining pattern, hence screening using HEp-2 substrate is unlikely to be a useful predictor for presence of these autoantibodies.